Atitudes dos servidores de uma Instituição Federal de Ensino Superior em Porto Alegre, diante da aposentadoria - Mai Junior, Luiz Carlos (2016)
This study investigated the attitudes of civil servants of a Brazilian federal institution of higher education regarding both, before his retirement and preparation for this transition. A standardized questionnaire to assess the expectations of the results of retirement (qualitative phase) and content validation of this questionnaire (quantitative phase) were carried out. The participants were 48 administrative technical servants. In the qualitative phase, thematic interviews with four participants allowed for the creation of the initial version of the Retirement Results Expectations Questionnaire (QERA-IFES). In the quantitative phase, content analysis was performed with 44 servants that rated each item on a Likert scale, clarity levels of language and relevance of the new questionnaire items were examined. Such levels of clarity and relevance allowed calculating the content validity coefficient (CVC). The coefficient showed a satisfactory performance with CVCt = 0.94 for the clarity scale and CVCt = 0.93 for the relevance of questionnaire, with a cut-off value of 0.70. The error value was 1.9 x 10 -96 (avalue considered = 0). The result of this study phase took into account new adaptation with two items being added, generating QERA-IFES/2 (20 items). Future studies should go further in this questionnaire validation processes, like predictive validity.